류마티스 관절염 환자에서 Conserved T 세포 수용체의 CDR3 motif를 표현하는 제2형 콜라겐 특이 T세포주의 형성과 유지 - 김승훈(Seung-Hoon Kim); 조미라(Mi-La Cho); 윤지희(Jeehee Youn); 박성환(Sung-Hwan Park); 조철수(Chul-Soo Cho); 황수연(Sue-Yun Hwang); 김호연(Ho-Youn Kim) (Immune network, 2001)
Background: To determine the molecular structure of type II collagen-specific T-cell receptors associated with rheumatoid arthritis (RA). Methods: We generated CII-specific T-cell lines of 8 RA patients by prolonged in vitro culture with bovine CII (bCII) and the immunogenic peptide (256-270) of human CII. The proliferation response towards CII stimulation was measured from the uptake of 3H-thymidine. Changes in the secretion of Th 1 and Th2 cytokines in the culture supernatent were measured by ELISA. The TCR clonotypes of these T-cells were examined by RT-PCR/SSCP analyses of all 22 $V_{β}$ chains. Results: T-cells from patients' tissue exhibited strong proliferation index upon CII stimulation, which was maintained up to 6 months in the culture. The secretion of INF-$γ$from these T-cells increased along with the duration of culture time, while the amount of IL-4 production did not show significant changes. The SSCP band patterns of patients' T-cells appear as discrete bands unlike the smeary streak produced from normal samples. Some SSCP bands, each representing selected expansion of a TCR containing certain subtype of $V_{β}$ peptides, appeared to be identical in more than one patients. Among these, the expansion of SSCP band representing the $V_{β}$ 14 CDR3 region persisted after switching the antigen to the immunogenic human peptide (256-270). Conclusion: CII-reactive T-cells expressing distinct CDR3 motifs are selectively expanded in the peripheral blood and synovial fluid of RA patients, and their persistent proliferation upon CII stimulation, as well as the production Th 1-type cytokines, may play pivotal roles in RA pathogenesis.